Tribo-Brake Characteristics between Brake Disc and Brake Shoe during Emergency Braking of Deep Coal Mine Hoist with the High Speed and Heavy Load - Dagang Wang; Ruixin Wang; Tong Heng; Guozheng Xie; Dekun Zhang (Energies, 2020)
The friction wear and thermal fatigue cracking of the brake shoe and friction-induced self-excited vibration (frictional flutter) of the disc brake can easily occur during emergency braking of a deep coal mine hoist with at high speed and with a heavy load. Therefore, tribo-brake characteristics between the brake disc and brake shoe during emergency braking of a deep coal mine hoist are investigated in the present study. Scaled parameters of the disc brake of a deep coal mine hoist are determined by employing the similarity principle. Friction tests between friction disc and brake shoe are carried out to obtain the coefficient of friction in the case of high speed and large specific pressure between the friction disc and brake shoe. Coupled thermo-mechanical finite element analyses of the brake disc and brake shoe are established to investigate temperature and stress fields of the brake disc and brake shoe during emergency braking, which is validated by the engineering failure case. Effects of braking parameters on flutter characteristics between the brake disc and brake shoe are explored by employing a double-degrees-of-freedom vibration mechanism model. The results show that the maximum temperature, equivalent Von Mises stress and contact pressure are all located at the average friction radii of contact surfaces of the brake disc and brake shoe during emergency braking. The cage crashing accident in the case of high speed and heavy load in a typical coal mine shows crack marks and discontinuous burn marks at central locations of brake shoe and brake disc surfaces, respectively, which indicates frictional flutter characteristics between brake disc and brake shoe. During emergency braking, flutter time duration decreases with increasing initial braking speed and damping parameter; the flutter amplitude and frequency of the disc brake increases with increasing normal braking load and stiffness, respectively.